2012
DOI: 10.1186/1471-2229-12-18
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel microRNAs in Hevea brasiliensisand computational prediction of their targets

Abstract: BackgroundPlants respond to external stimuli through fine regulation of gene expression partially ensured by small RNAs. Of these, microRNAs (miRNAs) play a crucial role. They negatively regulate gene expression by targeting the cleavage or translational inhibition of target messenger RNAs (mRNAs). In Hevea brasiliensis, environmental and harvesting stresses are known to affect natural rubber production. This study set out to identify abiotic stress-related miRNAs in Hevea using next-generation sequencing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 80 publications
3
66
1
Order By: Relevance
“…Further, we found that all homologs of 27 conserved miRNA families of castor bean in rubber tree, but we did not find any homolog of the 72 novel miRNAs identified from castor bean in other members of Euphorbiaceae including rubber tree [43], [44], Jatropha curcas [45] and Manihot esculenta [46], implying that the 72 novel miRNAs detected might represent castor bean species-specific miRNAs. Compared to the target genes identified in other plants, rco-miR167, rco-miR172 and rco-miR482 exhibited similar targets to their homologs in Arabidopsis [47] and maize [25].…”
Section: Discussioncontrasting
confidence: 57%
“…Further, we found that all homologs of 27 conserved miRNA families of castor bean in rubber tree, but we did not find any homolog of the 72 novel miRNAs identified from castor bean in other members of Euphorbiaceae including rubber tree [43], [44], Jatropha curcas [45] and Manihot esculenta [46], implying that the 72 novel miRNAs detected might represent castor bean species-specific miRNAs. Compared to the target genes identified in other plants, rco-miR167, rco-miR172 and rco-miR482 exhibited similar targets to their homologs in Arabidopsis [47] and maize [25].…”
Section: Discussioncontrasting
confidence: 57%
“…More recently, several high-throughput analyses have led to the identification of microRNAs [56], [57], transcriptomes [11], [58][60], and genomes [61] using NGS technologies. All the transcriptome analyses have provided a partial overview of the Hevea transcriptome, as RNAs from only a few specific tissues were sequenced, such as shoot apex [58] and leaf [61] from clone RRIM 600, along with leaf and latex from CATAS 7-33-97 [59].…”
Section: Discussionmentioning
confidence: 99%
“…miR828 is the trigger for production of TAS4 siRNAs, and was originally thought to be unique to Arabidopsis , but has subsequently been found in grape [55], poplar ( Populus trichocarpa ) [56], cotton ( Gossypium hirsutum ) [57], cabbage ( Brassica rapa ) [58], flax ( Linum usitatissimum ) [59], soybean ( Glycine max ) [21], common bean ( Phaseolus vulgaris ) [60], clary sage ( Salvia sclarea ) [61], melon ( Cucumis melo ) [62], rose ( Rosa multiflora ) [63], tomato ( Solanum lycopersicum ) [64], tobacco ( Nicotiana tabacum and N. attenuata ) [65, 66], cocoa ( Theobroma cacao ) [67], Chinese apricot ( Prunus mume ) [68, 69], peach ( Prunus persica ) [70, 71], citrus ( Citrus sinensis ) [72], apple ( Malus domestica ) [73], hickory ( Carya cathayensis ) [74], cassava ( Manihot esculenta ) [75], Brazilian cherry ( Eugenia uniflora ) [76], Chinese tulip tree ( Liriodendron chinense ) [77], and Red Sea mangrove ( Avicennia marina ) [78]. Figure 1 shows a phylogram of the evolutionary relationships for eudicot species which have evidence of TAS4 in their genomes.…”
Section: Tas4 Evolutionmentioning
confidence: 99%